Dual-axis solar tracker based on predictive control algorithms - Suria, A. K. (Institute of Electrical and Electronics Engineers Inc., 2016)
The paper presents the development of dual-axis solar tracker system based on predictive control algorithms. This prototype of solar tracker was tested and the result has shown the energy output of the solar panel increased by positioning a solar panel directly perpendicular to the sun and gaining the maximum sunlight intensity. The algorithm was programmed using Arduino ADK controller. The proposed solar time algorithm was used based on the sun's position and sending the signal to the motor, thus moving the tracker towards the sun automatically. The performance of the system was tested and compared with static solar panel. The results have shown that the solar tracker was increased the percentage harvesting of the PV generation around 21.4%.